The place of interest in education - Smith, Emily Gertrude (My University, 1906)
Introduction: Interest is a doctrine associated with many great minds, and has been discussed at length by many of the great educators of the present and the past. What is Interest? This is a question which, notwithstanding all this discussion, is yet incapable of exact definition. It is not a form of knowledge, it is not a kind of action; but it is a “feeling to be felt not defined” says De Garno. It is a feeling familiar to every growing mind, yet we cannot exactly define it. In his work in “Interest and Education,” De Garno defines interest thus “Interest is a feeling which accompanies the idea of self expression.” Hinsdale says, “Interest is the name given to the pleasurable or painful feelings which are evoked by an object or idea. Many other great writers also agree that interest is a feeling; a feeling of the real value of the end in view. If the end seems to us to be of great value, our interest will be proportionately great.
Citation: Smith, Emily Gertrude. The place of interest in education. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Education; Interest; Theses; Manuscripts (documents)